Bcl-2 and Bax interaction in B-lymphocytes of peripheral blood in patients with chronic lymphocytic leukemia - Brajušković Goran R.; Orolicki-Vukosavić Slobodanka; Cerović Snežana; Ušaj-Knežević Slavica; Marjanović Slobodan; Romac Stanka (Vojnosanitetski Pregled)
Background. Chronic lymphocytic leukemia (CLL) is a neoplastic disease characterized by the accumulation of morphologically mature monoclonal CD5+ B cells in the early phase (G0/G1) of the cell cycle. The accumulation of neoplastically transformed B-lymphocytes (CLL cells) is primarily the consequence of apoptosis blocking in these cells. Bcl-2 proteins are well-known modulators of this process. Some of these proteins are anti-apoptotic while the others are pro-apoptotic. All contain at least one of the four conserved regions called the Bcl-2 homologous domains (BH1-BH4). Evidence indicates that Bcl-2 and Bax form homo- and heterodimers. The anti-apoptotic effect of Bcl-2 protein is based on its ability to bind Bax protein in the heterodimer form, and thus to block the forming of Bax/Bax proapoptotic homodimers. The ratio of Bcl-2/Bax represents the cell autonomous rheostat which determinates the type of the cell reaction to an apoptotic stimulus. Methods. The aim of this study was to determine the level of interaction between these two proteins in CLL cells using the co-immunoprecipition method. The study included the analysis of 20 peripheral blood specimens from 20 patients with CLL, and 20 peripheral blood specimens from healthy persons, who were in the control group. Specimens were precipitated with the monoclonal antibody for Bcl-2 protein, and immunoblotted with the palyclonal antibody for Bax protein (IP: Bcl-2/WB:Bax). At the same time, specimens were precipitated with the polyclonal antibody for Bax protein, and immunoblotted with the monoclonal antibody for Bcl-2 protein (IP: Bax/WB:Bcl-2). The intensity of Bcl-2 and Bax protein's binding compared to the control samples of the peripheral blood from healthy persons, was increased in CLL cells. Results. IP: Bax/WB: Bcl-2 showed a high level of “free“ Bcl-2 protein which was not bound in the heterodimer form to Bax protein. Simultaneously IP: Bcl- 2/WB: Bax showed that a higher quantity of Bax protein was bound in the heterodimer form to Bcl-2 protein as opposed to the quantity of pro-apoptotic Bax protein potentially bound in the homodimer form. Conclusion. Further studies involving larger groups of patients are necessary to explore the potential significance of the Bcl-2/Bax protein ratio as a prognostic parameter in the CLL treatment.